Five-year follow-up of modified implant-supported overdenture in an iliac crest autograft failure: Clinical report - Pereira, Rodrigo dos Santos [UNESP]; Boos, Fernanda Brasil Daura Jorge [UNESP]; Lourenço, Eduardo José Veras; Hochuli-Vieira, Eduardo [UNESP]; Rodrigues, Paulo da Costa; Homsi, Nicolas (Wolters Kluwer, 2013)
The treatment of extensive pathologic lesions in the jaw, most of the time, can generate rehabilitation problems to the patient. The solid ameloblastoma is a locally invasive odontogenic tumor with a high recurrence rate. Its treatment is aggressive and accomplished through resection with safety margin. The criterion standard for reconstruction is autogenous bone, but it can provide a high degree of resorption, causing inconvenience to the patient because of lack of rehabilitative option. This study aimed to describe a patient with ameloblastoma treated through resection and reconstruction with autogenous bone graft, in which, after an extensive resorption of the graft was made, a modified bar was applied to support a prosthetic implant overdenture. Copyright © 2013 by Mutaz B. Habal, MD.
Keywords: Ameloblastoma; Dental implants; Dental prosthesis; Mandible